Technocracy as a form of consensus. Evidence from Santiago’s Public Transportation System. - Gartenlaub, Andrea (Estado, Gobierno y Gestión Pública, 2011)
The article seeks to demonstrate how in discussions over Santiago’s public transportation system technical knowledge was transformed into a consensus-building tool. It is argued that a consensus was built on the basis of shared social imaginaries, reflected in the discourse of officials and in the written press.